Pengembangan Booklet Terintegrasi Nilai Preventif Kesehatan Kardiovaskular untuk Peserta Didik Fase F SMA: Penelitian - Raisa Malika; Rahmadhani Fitri; Relsas Yogica; Helsa Rahmatika (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The increase in cardiovascular disease cases in productive age is related to the low awareness of adolescents in maintaining health. Learning in schools has the potential to instill an understanding of preventive values, but based on the findings of learning media that are generally utilized, it has not optimally contained these values. The purpose of this study was to develop an integrated booklet of cardiovascular health preventive values for Phase F high school students that is valid and practical. This type of research is Research and Development (R&D) with reference to the initial three stages in the 4-D development model. The subjects involved in this study consisted of two lecturers of Biology FMIPA UNP, two Biology teachers, and 31 students of SMAN 1 Batusangkar. The object of the research is a booklet integrated with preventive value of cardiovascular health. The main data in the study were obtained directly through interview sheets, needs analysis questionnaires, knowledge questionnaires, validity questionnaires, and practicality questionnaires. The data were analyzed using a quantitative descriptive approach. The results of data analysis showed a validity percentage of 91.78% (very valid) and a practicality percentage of 95.31% (very practical) by teachers and 90.31% (very practical) by students.